2021
DOI: 10.47740/563.udsijd6i
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Technology Adoption by Traditional African Vegetable Farmers in Northern Ghana

Abstract: The production of traditional African vegetables is an age-old tradition among the people of the northern region of Ghana. However, the knowledge base of traditional African vegetable production remains local due to a lack of research and policy support. Therefore, the adoption of improved technology among traditional vegetable farmers is generally low and impedes efforts to promote widespread cultivation, consumption and even commercialisation. This study aims at clarifying potential factors that determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…This finding corroborates the study of Kpodo et al [43], who reported that cocoyam leaf, okra and garden egg are among the most commonly consumed vegetables in Ghana. Issaka et al [44] also reported similar IVs in Northern Ghana. The extensive consumption of these IVs could be attributed to the fact that they are complements to most of the cereal-based staples including banku, tuo zaafi, kenkey, etc.…”
Section: Range Of Ivs Consumedmentioning
confidence: 65%
“…This finding corroborates the study of Kpodo et al [43], who reported that cocoyam leaf, okra and garden egg are among the most commonly consumed vegetables in Ghana. Issaka et al [44] also reported similar IVs in Northern Ghana. The extensive consumption of these IVs could be attributed to the fact that they are complements to most of the cereal-based staples including banku, tuo zaafi, kenkey, etc.…”
Section: Range Of Ivs Consumedmentioning
confidence: 65%
“…Mulching Barriers include: lack of contact with extension workers; land tenure and ownership constraints; and labor-intensive practice. [139,140] Improved seed (and GM seed)…”
Section: Agroforestrymentioning
confidence: 99%
“…In addition, average years of experience in vegetable production on a commercial scale was found to be higher (5.8) than the subsistence growers (2.71). In this line, Issaka et al (2021) stated the experience had a significant impact on yield. The expertise in production acquired from experiences would be supportive to scale up the production.…”
Section: Status Of Vegetable Growersmentioning
confidence: 99%